Pengaruh Model Pembelajaran Superitem terhadap Kemampuan Penalaran Matematis Siswa Kelas X IPA SMAN 1 Lembah Melintang Tahun Pelajaran 2021/2022 - Rodiatun Ulsiyah DN; Aniswita Aniswita (Departement of Mathematics Education, 2023)
This study uses the Superitem learning model learning model. The formulation of the research problem is